Severe complication due to inappropriate use of polymethylmethacrylate: a case report and current status in Brazil - Kleber Tetsuo Kurimori; Monique Mendes; Dimas André Milcheski; Araldo Ayres Monteiro; Rolf Gemperli (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: Use of permanent fillers can lead to significant complications. In Brazil, polymethylmethacrylate (PMMA) is a product approved by the Agência Nacional de Vigilância Sanitária (ANVISA), but its use exceeds its indications, leading to serious complications. Recommendations for restricted use have been in place for more than a decade, but cases with serious consequences due to inappropriate use are still seen. Objective: To report a serious complication due to inappropriate use of PMMA and discuss the current status of PMMA use in Brazil based on recommendations of medical societies and regulatory agencies. Methods: This report describes a case of extensive necrosis of the gluteal region after injection of PMMA by a non-qualified practitioner; the report also reviews the literature on the current status of PMMA use in Brazil. Discussion: Despite the efforts of medical societies, acute and chronic complications are still reported in the Brazilian literature. In 2016, more than 17,000 PMMArelated complications were reported; nevertheless, reliable epidemiological data remain unavailable because the number of treatments, the quality of the product, and the training of practitioners remain unregulated. Conclusion: A significant number of repair procedures are performed in Brazil to correct complications resulting from the use of PMMA. The severity of the reported case highlights the need to combat bad practice by untrained professionals, as well as the need for greater control of PMMA marketing by regulatory agencies.